Comparison of the Effectiveness of Mathematical Thinking Intervention and Dual Balance Training on the Quantitative Reasoning of Students with Mathematical Learning Disabilities - Safarzadeh, Teyebeh; Jajarmi, Mahmoud; Mahdian, Hossein (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The objective of this study was to compare the effectiveness of a mathematical thinking intervention and dual balance training on the quantitative reasoning abilities of students with mathematical learning disabilities (MLD). Methods and Materials: The study was a semi-experimental design with a pre-test, post-test, and follow-up with two experimental groups and one control group. A total of 45 students with MLD were selected through purposive sampling and randomly assigned to the mathematical thinking intervention group (n = 15), the dual balance training group (n = 15), and the control group (n = 15). The tools used for data collection included the KeyMath Test for quantitative reasoning and the Wisconsin Card Sorting Test for cognitive flexibility. Repeated measures analysis of variance (ANOVA) and Bonferroni post hoc tests were used to analyze the data across three test phases (pre-test, post-test, follow-up). Findings: Significant improvements were observed in the quantitative reasoning scores of both the mathematical thinking intervention group (F(1.48) = 919.50, P < .001, η² = 0.97) and the dual balance training group (F(1.48) = 88.25, P < .001, η² = 0.76) compared to the control group. The mathematical thinking group showed greater improvements from pre-test to post-test (M = -26.60, P = .001) and from pre-test to follow-up (M = -26.13, P = .001) compared to the dual balance training group (pre-test to post-test: M = -13.87, P = .001; pre-test to follow-up: M = -13.93, P = .001). Conclusion: Both the mathematical thinking intervention and dual balance training were effective in improving the quantitative reasoning of students with MLD. However, the mathematical thinking intervention showed greater efficacy, suggesting that cognitive-based interventions have a stronger impact on mathematical reasoning than physical-based interventions.